Handbook of Lizards : Lizards of the United States and of Canada - Smith, Hobart M. (Hobart Muir), 1912-2013 (Book collections on Project MUSE., 1995)
The most thorough treatment of lizards of the United States and Canada when first published in 1946, Handbook of Lizards has become a landmark among herpetologists and lizard specialists. Hobart M. Smith spent years compiling and organizing information on 136 species of lizards for this classic study. With more than 300 illustrations, including black-and-white photographs, labeled drawings, range maps, and illustrated keys, this volume serves as a still-relevant and convenient reference guide to the study of North American lizards. Darrel Frost, a prominent lizard specialist, provides a foreword for the 1995 paperback edition that underscores the work's relevance for herpetology today. In the first section, Smith covers in concise fashion the habits, life history, habitats, methods of collection and preservation, and structural features of lizards. The second section of the book considers each species under topics that are conveniently arranged for studying both living lizards and laboratory specimens: range, type, locality, size, color, scalation, recognition characters, habitat and habits, and references. Smith also discusses problems for further study and gives recommendations for special investigations of each species. The book concludes with an extensive bibliography.